Instrumental music and the Industrial Revolution - International Conference "Instrumental Music and the Industrial Revolution" 2006 Cremona, Italy); Illiano, Roberto; Sala, Luca (Bologna UT Orpheus, 2010)
In this volume we wanted to investigate the intersection between the Industrial Revolution and the aesthetic-musical field. In particular, we aimed to explore the European dimension of the cultural exchanges caused by the phenomenon of musical migration, together with the international relationships generated by the music printing industry, entrepreneurship and the market for musical instruments.The later eighteenth and earlier nineteenth centuries were a time of fundamental change in European life, proceeding from the revolutionary implications of the ideologies of Enlightenment, and reverberating in market economies, methods of manufacturing and agriculture, modes of travel, and population distribution. The development of new technologies resulted in the enlargement and improvement of the music printing industry, and in the widespread diffusion of music in private and public spheres.The Industrial Revolution brought about the ‘modernization’ of productive processes and, as a consequence, engendered a kind of ‘globalization’ of the musical market.(taken from: https://www.luigiboccherini.org/2010/05/01/instrumental-music-and-the-industrial-revolution/)
Selected papers presented at a conference held in Cremona, Italy, July 1-3, 2006.
Essays by Luca Aversano, Claudio Bacciagaluppi, Carmela Bongiovanni, Andrea Cardone, Jen-yen Chen, Simone Ciolfi, Andrea Coen, Therese Ellsworth, Joël-Marie Fauquet, Florence Gétreau, Consuelo Giglio, Outi Jokiharju, Roe-Min Kok, Paul R. Laird, Marie Sumner Lott, Simon McVeigh, Elio Matassi, Russ Manitt, Jenny Nex, Leon Plantinga, Alban Ramaut, Rudolf Rasch, David Rowland, Laure Schnapper, Rohan H. Stewart-MacDonald, Renata Suchowiejko, Maria Alice Volpe.
Includes bibliographical references and index.
Contributions in English, French, and Italian.
Keywords: 18th Century (1701-1800); 19th Century (1801-1900); Instrumental music; Music history; Music philosophy and esthetics; Technology; Music printing; Sociology